The Threat of Protected Flora and Fauna Smuggling In Indonesia as A Transnational Organized Crime From The Perspective of Customs and Excise - Zul Faqqaur Ananta Yudha, Firdaus; Hanita, Margaretha; Riyanta, Stanislaus (Asian Journal of Social and Humanities, 2024)
This article began with the existence of a major threat to national resilience related to transnational organized crime (TNOC) in wildlife trade and smuggling. The Directorate General of Customs and Excise (DJBC) as the guard of Indonesia's entrance has a strategic role in efforts to supervise TNOC activities. This study aims to analyze the threat of TNOC acts of animal smuggling and all efforts made by DJBC with other law enforcement officials. This paper uses a qualitative approach, with the research method of literature study or document study. Data collection techniques come from secondary data such as related institutional documents and literature that are in accordance with the concepts discussed. The results of the study show that the threat of wildlife smuggling is still very high which has the potential to pose a great risk to national resilience in the context of biodiversity conservation, community protection from various viruses to economic losses that Indonesia can get. From the perspective of strategic intelligence, the supervision of TNOC actions requires various strengthening, especially in strengthening data and intelligence information systems, strategic intelligence resources and creative thinking of law enforcement. Finally, various efforts to strengthen the legal foundation require dynamic efforts by adjusting environmental conditions and international laws and regulations, accompanied by synergy between institutions.